Searching for an immunogenetic factor that will illuminate susceptibility to non-tuberculous mycobacterial disease - Affandi, J.; Hendry, S.; Waterer, G.; Thomson, R.; Wallace, H.; Burrows, S.; Price, Patricia (2013)
The incidence of pulmonary non-tuberculous mycobacteria (NTM) disease in otherwise healthy adults is increasing as the population ages. The organisms are ubiquitous so susceptibility probably reflects a deficiency in a protective immune response. Here we investigate if singlenucleotide polymorphisms (SNP) affecting cytokines, chemokines and their receptors associate with pulmonary NTM disease. Samples from NTM patients (n=79) and healthy controls (n=188) were genotyped using TaqMan probes. Of the 16 SNPs assessed, IL28B-rs8099917*TG (rs8099917; P=0.01, OR=2.2), TNFA-1031*CC (rs1799964; p=0.02, OR=0.48) and IL10-1082*AA (rs1800896; P=0.001, OR=0.33) were significantly associated with NTM disease. IL28B-rs8099917 and IL10-1082 have been associated with perturbations of the Th1/Th2 balance, whilst TNFA-1031*CC associates with sensory neuropathy in HIV patients. IL10-1082 warrants further investigation because we observed high production of IL-10 in blood mononuclear cells from NTM patients. © 2013 American Society for Histocompatibility and Immunogenetics.